Respuesta :
Answer:
x=-2 x=-1
Step-by-step explanation:
2x^2 + 6x = -4
Add 4 to each side
2x^2 + 6x +4= -4+4
2x^2 + 6x +4=0
Factor out 2
2( x^2 +3x+2) = 0
Divide by 2
x^2 +3x +2 =0
( x+2)(x+1) =0
Using the zero product property
x+2 =0 x+1 =0
x=-2 x=-1
Answer:
x = -1, -2
Step-by-step explanation:
Bring the constant term to the left hand side :
- 2x² + 6x = -4
- 2x² + 6x + 4 = 0
Divide throughout by 2 :
- (2x² + 6x + 4)/2 = 0/2
- x² + 3x + 2 = 0
Splitting the middle term :
- x² + x + 2x + 2 = 0
- x(x + 1) + 2(x + 1) = 0
Factors obtained :
- (x + 1)
- (x + 2)
Finding the zeros :
- x + 1 = 0 ⇒ x = -1
- x + 2 = 0 ⇒ x = -2